Inventory of Solanaceae Family Plants in Goalpara Sukabumi - Wulan Anggraeni; Yesti Nuralisa; Ateng Supriyatna (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Solanaceae is a plant that belongs to the eggplant tribe where Solanaceae is also known as a flowering plant where this plant includes various types of eggplant, tomatoes and cayenne pepper. In this study, the aim was to determine the morphology, anatomy and types of plants belonging to the Solanaceae family. The tools and materials used in this study were a camera to document stationery for recording and materials in the form of plants to be observed for their morphology and anatomy. in this study using the random roaming method or exploring in the goalpara Sukabumi area to look for plants or plants that belong to the solanaceae after which it is documented and recorded. The results obtained where three plants belonging to the Solanaceae family were found, namely chili, purple eggplant and American Black Nightshade.